Laboratory automation, informatics, and artificial intelligence: current and future perspectives in clinical microbiology - Mencacci, Antonella; De Socio, Giuseppe Vittorio; Pirelli, Eleonora; Bondi, Paola; Cenci, Elio (Frontiers in Cellular and Infection Microbiology, 2023)
Clinical diagnostic laboratories produce one product—information—and for this to be valuable, the information must be clinically relevant, accurate, and timely. Although diagnostic information can clearly improve patient outcomes and decrease healthcare costs, technological challenges and laboratory workflow practices affect the timeliness and clinical value of diagnostics. This article will examine how prioritizing laboratory practices in a patient-oriented approach can be used to optimize technology advances for improved patient care.